DEVELOPMENT OF TRANSCUTAN DELIVERY OF SODIUM ASCORBYL PHOSPHATE NANOEMULSION WITH SOLID-IN-OIL DISPERSION - Khaira Nursal, Fith
The delivery system of active substance through the skin transcutaneously or transdermally is limited by the size, molecular weight and also molecular affinity of the skin layer composed of lipid components. Theoretically, hydrophilic molecules experience permeation resistance into the skin layer and it is needed specific technique in its delivery. Through the solid-in-oil dispersion (SOD) these obstacles were successfully overcome and many studies have been proven that hydrophilic protein macromolecules could be delivered through the skin using the SOD technique in nanoformulation preparations. Sodium ascorbyl phosphate (SAP) is a vitamin C derivative compound that is hydrophilic with the low permeability (log Pow at 10 -4 ), thus inhibiting the permeation in the stratum corneum (SC) layer. The purpose of this study is to increase the permeation of SAP through increasing dispersibility in oil with the SOD technique by combining it with amphiphilic compounds. In this study lecithin (soy lecithin) and polyethylene glycol (PEG) 20000 were used. Amphiphilic compounds will form a layer around the active substance which is hydrophilic so that it is partitioned stronger in the oil phase. The formation of SOD began by mixing the active substances with amphiphilic compounds, and coliophilization. Two different techniques have been carried out, group I was formed through a system of solution/dispersion of SAP-lecithin and SAP-PEG 20000 within water. Group II was formed by beginning with the formation water in oil (W/O) emulsions between SAP-VCO and lecithin, and varied with the addition of Tween 80. Each group was dried through freeze drying to remove water from the mixture so that SOD was formed and called lyophilizate. The results of lyophilizate I were white powder (SAP-PEG 20000) and semisolid form like a caramel (SAPlecithin), while lyophilizate II was an oily liquid. Lyophilizate analysis with Fourier Transmission Infra Red (FTIR) was carried out to see the interaction of SAP with amphiphilic compounds. The spectrum showed that the interaction of SAP with lecithin and PEG 20000 did not form new compounds, but formed an electrostatic charge from ion pairs between negatively charged phosphate groups on SAP molecule with positively charged choline groups from lecithin. This interaction makes the surface on SAP-lecithin. The morphology of lyophilisate through Transmission Electron Microscopy (TEM) indicates the presence a layer of lecithin on the surface of SAP, overall. The next step was to incorporate lyophilizate within oil in water (O/W) nanoemulsion, was made based on the lyophilizate group. Glycerin was added to NE I to increase the dispersibility of lyophilizate in the oil phase, and lyophilizate II was incorporated without the addition of glycerin in NE II. The addition of glycerin in NE I had a significant effect on SAP diffusion ability because glycerin increased the solubility of SAP in oil (VCO). Physically, NE I was clearer than NE II because of the addition of glycerin. Morphological observations of preparations through TEM showed that lecithin was on the surface of the active substance SAP between oil-water. Measurement of globule diameter, polydispersity index (PDI) and potential zeta were carried out at room temperature (± 25 °C) and storage in a climatic chamber (± 40 °C / RH 75%). The average globule’s diameter among formula of NE I at room temperature was ± 100-200 nm with the PDI value 0.2-0.4. The average globule’s diameter among several formulas in NE II was in ranges from ± 150-170 nm with the PDI value 0.2-0.5. There was no significant difference between average globule’s diameter and polydspersity index at room temperature (P> 0.05). Storage in the climatic chamber causes an increase in the diameter of the globule triggered by the influence of temperature so that globule mobility occurs, thus forming a coalescent with globule diameter mean values significantly different (P <0.05) and PDI values 0.1-0.4 (not significantly different from P > 0.05). Determination of the active substance was determined by a previously validated analytical method using high performance liquid chromatography (HPLC). The NAF levels in the sample decreased significantly during room temperature storage with a P value <0.05. Penetration studies were done through in vitro diffusion tests with Franz diffusion cells using Spangler membranes and snake skin membrane using Python Reticulus sheed snake skin. The results of diffusion of SAP within NE I with the addition of glycerin increased the diffusion of SAP between formulations reached out ± 80% at 6 th hour. SAP diffusion within NE II among formulas was attained ± 50% until the 8 th hour and overall had significantly differences (P <0.05). Diffusion result of NE II demonstrated that the SOD system could increase SAP diffusion ± 20% higher than SAP without SOD. The internalization study of sample for fibroblast cells through fuorochrome nile-red staining proved the ability of NE sample with an oil base, after crossing the SC layer it can accumulate in the cytoplasm and permeated to dermis layer. The anti-wrinkle activity test on human subjects used two formula, namely the NE F3 formula which was made SAP with SOD and formula NE SAP II was made without the treatment of SOD. The decrease in wrinkle values in the subjects occurred after 28 days of uses, but did not differ significantly (P> 0.05). Further experiments, showed no significant difference between the two samples in decreasing wrinkle value (P = 0.676).